1994
DOI: 10.1155/s0962935194000244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ursolic Acid and its Analogues on Soybean 15‐LipoxygenaseActivity and the Proliferation Rate of A human Gastric Tumour Cell Line

Abstract: The authors have previously isolated and purified ursolic acid from heather flowers (Calluna vulgarts). This terpene was found to inhibit HL-60 leukaemic cell proliferation and arachidonic acid oxidative metabolism in various cell species. The effects of ursolic acid and its analogues on soybean 15-lipoxygenase activity and on the proliferation of a human gastric tumour cell line (HGT), have been assessed. These triterpenes inhibited soybean 15-lipoxygenase at its optimal activity (pH 9). The proliferation ofH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
(3 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, studies have revealed that several species from Ericaceae plants such as Calluna vulgaris L., Ledum groenlandicum Retzius and Vaccinium mirtillus L. possess in vivo anti-inflammatory activity (Lietti et al, 1976;Es-Saady et al, 1994;Dufour et al, 2007;Orhan et al, 2007). In the current study, anti-inflammatory and antinociceptive activities of the extracts from Erica arborea, Erica bocquetii, Erica manipuliflora and Erica sicula subsp.…”
Section: Introductionmentioning
confidence: 50%
“…On the other hand, studies have revealed that several species from Ericaceae plants such as Calluna vulgaris L., Ledum groenlandicum Retzius and Vaccinium mirtillus L. possess in vivo anti-inflammatory activity (Lietti et al, 1976;Es-Saady et al, 1994;Dufour et al, 2007;Orhan et al, 2007). In the current study, anti-inflammatory and antinociceptive activities of the extracts from Erica arborea, Erica bocquetii, Erica manipuliflora and Erica sicula subsp.…”
Section: Introductionmentioning
confidence: 50%
“…Numerous studies have been published on the possible biological activity of this acid and its glucosides. It has been studied in its activity as an inhibitor of the proliferation of leucemic cells (Es-Saady et al, 1994), as a hypoglucemiant (Yoshikawa et al, 1994), as an anti-tumoral agent (Gerhauser et al, 2003), as a hepatoprotective agent (Yim et al, 2001), as an anti-inflammatory (Ismaili et al, 2002;Takeoka et al, 2000 andChoi et al, 2002), as an anti-bacterial (Sasazuka et al, 1995), as an inhibitor of the production of nitric acid (Honda et al, 1997), as an anti-HIV agent (Mengoni et al, 2002), in its anti-atherogenic activity (Somova et al, 2003) and as a cardiotonic (Somova et al, 2004). Also in existence are publications and patents for the preparation of functional foods with oleanolic acid (Hassel et al, 1998;Putte, 2000;Guinda et al, 2004).…”
Section: Terpenic Componentsmentioning
confidence: 99%
“…In addition, the leaf contains a considerable amount of terpenic compounds, whose biological activity is well-known. A specific review of the pharmacological activity of oleanolic acid has been published (Tian et al, 2002), as well as a study of the anticarcinogenic effect of ursolic acid (Es-Saady et al, 1994, 1996ay 1996b. Basically, the leaf represents a by-product whose potential for use is still under development.…”
Section: The Benefits Of Extractsmentioning
confidence: 99%
“…The SBL inhibitory activity of isolates 1-6 are being reported for the first time. Ursolic acid (7) (Es-Saady et al, 1994) and daucosterol (8) (Kim et al, 2006) were already reported for their in vitro 15-LOX and 5-LOX inhibition respectively. Among the other isolates, friedelin (2) showed comparable SBL inhibitory activity (IC 50 35.8 M) with NDGA (IC 50 32.7 M), whereas 3␤-hydroxyglutin-5-ene (1), cycloeucaneol (3), nimbiol (4), sugiol (5), surianol (6) ursolic acid (7) and daucosterol (8) showed moderate SBL inhibitory activity with IC 50 84.0, 54.3, 106.0, 60.7, 175.7, 92.8 and 108.7 M respectively.…”
Section: Resultsmentioning
confidence: 98%